2021
DOI: 10.3390/vaccines9121405
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vaccine Hesitancy, eHealth Literacy, and Vaccine Literacy in Young Adults’ COVID-19 Vaccine Uptake Intention in a Lower-Middle-Income Country

Abstract: Various control measures, including vaccination, have been taken to flatten the COVID-19 epidemic curve across the globe. However, in Bangladesh, many young adults, considered the asymptomatic transmitter of the disease, are waiting to get their first shot. Therefore, the potential predictors of the young adults’ vaccine uptake intention are significant to ensure their maximum vaccination when available to them. This study examined how vaccine hesitancy, eHealth literacy, and vaccine literacy are associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…Next, the vaccine non-hesitant participants in our sample had significantly higher scores of functional, communicative, and critical literacies as opposed to hesitant participants. This finding is consistent with one study which was performed in Bangladesh, in which individuals with higher vaccine literacy had the greater vaccine acceptability [ 40 ]. This can be explained by the premise that individuals with high vaccine literacy will be able more efficient in distinguishing false from accurate information.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Next, the vaccine non-hesitant participants in our sample had significantly higher scores of functional, communicative, and critical literacies as opposed to hesitant participants. This finding is consistent with one study which was performed in Bangladesh, in which individuals with higher vaccine literacy had the greater vaccine acceptability [ 40 ]. This can be explained by the premise that individuals with high vaccine literacy will be able more efficient in distinguishing false from accurate information.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies suggested that rural area residents have less general vaccine confidence and a few opportunities to gain access to health literacy regarding COVID-19 and vaccination [ 37 , 38 ]. Being culturally conservative and less educated, rural residents are more likely than urban residents to accept misinformation and conspiracy theories [ 38 , 39 , 40 , 41 ]. Additionally, the healthcare access in rural areas may not be adequate to provide large scale care to COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, future studies are warranted to explore the mechanisms underlying the effects of health literacy on vaccination. A recent study has found that both vaccine literacy and ehealth literacy were associated with greater vaccine uptake intention among younger adults in a lower-middle-income country [70] , suggesting different types of health literacy should also be investigated in undrestanding people’s vaccine-related attitude and behaviors. Given the important role of contextual factors, it is still inconclusive whether our findings could be transferred to people in different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Even party elite can help to increase the vaccination intention, through the way of cues ( 15 ). There is also a study which took the opinion leader as a control variable, and found that they are significantly and positively correlated with COVID-19 vaccine uptake intention ( 16 ). In the research conducted by Shmueli, he found that opinion leaders on social media expressing support can benefit the vaccination intention ( 17 ).…”
Section: Literature Reviewmentioning
confidence: 99%